2020
DOI: 10.1002/pat.4954
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aspect ratio of vertically aligned copper nanowires in the presence of cellulose nanofibers on the thermal conductivity of epoxy composites

Abstract: The composites comprising vertically aligned network of copper nanowires (CuNWs) in the presence of cellulose nanofibers were fabricated by using the freeze‐templating method and the effect of aspect ratio (A/R) of CuNWs on the thermal conductivity of epoxy composites was investigated. The thermal conductivity of epoxy composites increased to 0.79 W m−1 K−1 at 1.12 vol% of high A/R CuNWs loading, corresponding to the thermal conductivity enhancement of 365% as compared to the pure epoxy. The thermal conductivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…74,75 In this context, the discontinuity of giant reed fiber networks in the perpendicular path tends to slightly enhance thermal conductivity as incrementing the fiber concentration up to 10 wt.%. 76
Figure 9.Thermal conductivity of giant reed fiber–PET biocomposites.
…”
Section: Resultsmentioning
confidence: 99%
“…74,75 In this context, the discontinuity of giant reed fiber networks in the perpendicular path tends to slightly enhance thermal conductivity as incrementing the fiber concentration up to 10 wt.%. 76
Figure 9.Thermal conductivity of giant reed fiber–PET biocomposites.
…”
Section: Resultsmentioning
confidence: 99%
“…Graphene in any form could improve the thermal conduction performance of EP composites more effectively than CNTs, graphite nanoplatelets, and carbon black, as shown in Figure 3. Thieu et al 69 reported the effect of the aspect ratio of copper nanowires (CuNWs) on the TC of EP composites. The TC of the composites containing 1.12 vol% CuNWs with a high aspect ratio was 0.79 Wm −1 K −1 , while the TC of composites with a low aspect ratio of CuNWs was only 0.54 Wm −1 K −1 at the same loading.
Figure 3.Effect of various carbon nanofillers on the effectiveness of the improvement in thermal conductivity of epoxy matrix composites at room temperature relative to that of the neat epoxy resin.
…”
Section: Factors Affecting Tc Of Polymer Compositesmentioning
confidence: 99%
“…[352] In addition to the typical 2D graphene, BN and SiC sheet, 1D SiC microwires (SiCMWs), SiC nanowires (SiCNWs), CFs and copper nanowires (CuNWs) as well as aluminum nitride (AlN) particles have been developed for the preparation of epoxy composites with enhanced through-plane thermal conductivity by means of icetemplating method. [353][354][355][356][357] For example, Yao et al [354] has prepared a series of vertically aligned and interconnected SiCNW network structures by adjusting the proportion of components and infiltrated them with epoxy matrix. The final composites exhibit a high through-plane thermal conductivity up to 1.67 W m −1 K −1 at a relatively low filler loading (2.17 vol %).…”
Section: Thermally Conductive Compositesmentioning
confidence: 99%